Comparison of outcomes between below and above elbow plaster casts in treating fracture of distal radius - Nik Moho Fatmy, Nik Mohd Najmi (2011)
Fractures of distal radius are very common, and usually due to fall on outstretched hand. They account for more than one sixth of all fractures seen in the emergency department. In general, these fractures can be divided into either intra articular or extra articular fractures. Extra articular fracture is usually considered as stable and can be treated conservatively with casting. The current standard of casting is to apply an above elbow cast. With this type of casting however, one has to immobilize the elbow joint. Most of the patients in our local community tend to refuse this type of casting because of the heaviness, discomfort and also limitation of elbow movement. They prefer a below elbow cast and question whether this type of casting is adequate to treat their fracture. So this study, with the title of "Comparison of Below and Above Elbow Casts in Treating Fracture of Distal Radius", will try to answer this question. On the other hand, if this type of casting is acceptable, health centers will have the benefit in term of cost saving as the quantity of Plaster of Paris used during the procedure is less. 40 patients were recruited for this study, 20 in each group. Patients for below elbow cast group were recruited during the study period (January 2010 to October 201 0) when they registered for treatment at Emergency Department for distal radius fractures. Patients for above elbow cast group were selected from those who came for treatment of distal radius fractures within six months prior to the study period (ie from July 2009 to December 2009). Both groups were compared in term of radiological outcome and also functional outcome. The functional outcome assessment was done using a Mayo Wrist Score. The results showed that below elbow cast was as good as above elbow cast in treating fracture of distal radius. In fact, statistical analysis showed that below elbow cast was better than above elbow cast both in radiological and also functional assessment. Both types of cast were able to hold the fracture within acceptable range, but below elbow cast groups was able to maintain the initial reduction in 40% of patients compared to 35% only in above elbow cast. As for the functional assessment with the Mayo Wrist Score, below elbow cast group has an average score of 74 while above elbow cast group score is 69.5. In conclusion, even though it was not statistically significant, the results proved the hypothesis of this study, which is, below elbow cast is not inferior compared to above elbow cast in treating distal radius fracture.